Analysis of the 2010–2012 results of the multicenter external proficiency study for 25-hydroxyvitamin D. (October 2013) - Bianchi, Sara; Giovannini, Stefania; Zucchelli, Giancarlo; Clerico, Aldo; Pierini, Martina; Ndreu, Rudina; Vannucci, Alessandro; Battaglia, Debora; Vassalle, Cristina
Background: Results collected from the 2010–2012 cycles of the 'Immunocheck' external quality assessment scheme for 25-hydroxyvitamin D, conducted by QualiMedLab CNR (Italy) and ProBioQual (France; 250 among Italian and French laboratories) are presented in this article.Methods: Details of how QualiMedLab operates can be found in QualiMedLab website.Results: Interlaboratory imprecision was 19 (2010), 15 (2011) and 13% (2012). The LIAISON ® analyzer (DiaSorin, Italy) was the most utilized, followed by Roche (UK), ImmunoDiagnostic Systems methods (UK), ARCHITECT (Abbott, IL, USA), radioimmunoassay (DiaSorin) and others. The within-method variability between laboratories (percentage coefficient of variation) were 15, 12.7 versus 9.8% for LIAISON, 27.8, 16.5 versus 11.7% for Roche, 15, 12 versus 17% for ImmunoDiagnostic Systems and 17.4, 18.6 versus 17.5% for radioimmunoassay in the 2010, 2011 versus 2012 cycles, and 15 versus 8.9% for ARCHITECT in the 2011 versus 2012, respectively.Conclusion: Significant differences in specific samples and discrepancies between laboratories and methods still exist, making the actuation of appropriate external quality assessment schemes mandatory.